Chalcogenide phase change materials and their use - Borisenko, K (World Intellectual Property Organization, 2011)
According to the present invention there is provided a chalcogenide phase change material which can be converted between first and second states, wherein the material comprises a chiral species and wherein at least a portion of the material comprises the chiral species in the form of an enantiomeric excess. Methods of producing and analysing said material, as well as optical recording media and phase change memory devices comprising said material, are also provided.